Chromophore relaxation in a side-chain methacrylate copolymer functionalized with 4-[N-ethyl-N-(2-hydroxyethyl)]amino-2 '-chloro-4 '-nitroazobenzene - Ribeiro, P. A.; Balogh, D. T.; Fonseca, JLC; Giacometti, J. A. (Amer Chemical Soc, 2004)
A side-chain methacrylate copolymer functionalized with the nonlinear optical chromophore 4-[N-ethyl-N-(2-hydroxyethyl)]amino-2'-chloro-4'-nitroazobenzene, disperse red-13, was prepared and characterized. The chromophore relaxation was investigated measuring the decay of the electrooptic coefficient r(13) and the complex dielectric constant at different temperatures. Results obtained below and above T-g were analyzed using the Kohlrausch-Williams-Watts(KWW) equation, through the study of the temperature dependence of the KWW parameters. Above T-g the relaxation time experimental data were fitted to the Williams-Landel-Ferry (WLF) equation and its parameters determined. Chromophore relaxation leading to the decrease of electrooptic properties was found associated with a primary alpha relaxation. The obtained WLF equation parameters were introduced into the Adam-Gibbs-Tool-Narayanaswamy-Moynihan equation, and the overall relaxation time temperature dependence was successfully obtained in terms of the fictive temperature, accounting for the sample thermal treatment and allowing optimized thermal treatment to be found. The copolymer KWW stretching parameter at the glass transition temperature lies close to the limit value for short-range interactions, i.e., 0.6, suggesting that the chromophore group is participating in primary a relaxation.